Enterprise project portfolio management : building competencies for R&D and IT investment success - Bayney, Richard M.; Chakravarti, Ram (Ft. Lauderdale, FL : J. Ross Pub., 2012)
Offers a practical framework for implementing project portfolio management in R&D and IT enterprises. This title presents a structured framework for practitioners and students of project, program, and portfolio management to enhance their strategic and analytic capabilities in the evolving discipline of project portfolio management (PPM).
Includes bibliographical references (p. 349-350) and index.
oif 23/06/15
Loans
Keywords: Project management; Portfolio management; Enterprise project; Portfolio management - case studies; Project management.- building competencies